2020
DOI: 10.1186/s12966-020-00927-6
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of diet, physical activity, television exposure and sleep habits and their association with adiposity in preschool children: the EDEN mother-child cohort

Abstract: Background: Despite the growing interest in the relation between adiposity in children and different lifestyle clusters, few studies used a longitudinal design to examine a large range of behaviors in various contexts, in particular eating-and sleep-related routines, and few studies have examined these factors in young children. The objectives of this study were to identify clusters of boys and girls based on diet, sleep and activity-related behaviors and their family environment at 2 and 5 years of age, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 50 publications
4
44
1
1
Order By: Relevance
“…Older children’s sleep may have increased from a lack of formal school start times, akin to delaying school start times [ 30 ], which is not as rigid in preschools. This imbalance of movement behaviors is particularly concerning given evidence that preschoolers who do not meet movement guidelines over the long-term experience negative consequences of higher adiposity [ 42 ], lower educational outcomes [ 5 ], and compromised physiological development [ 5 ], and the COVID-19 outbreak is creating a long-term challenge to household routines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older children’s sleep may have increased from a lack of formal school start times, akin to delaying school start times [ 30 ], which is not as rigid in preschools. This imbalance of movement behaviors is particularly concerning given evidence that preschoolers who do not meet movement guidelines over the long-term experience negative consequences of higher adiposity [ 42 ], lower educational outcomes [ 5 ], and compromised physiological development [ 5 ], and the COVID-19 outbreak is creating a long-term challenge to household routines.…”
Section: Discussionmentioning
confidence: 99%
“…Creation of a valid and reliable questionnaire to thoroughly assess 24-h movement guideline adherence in this age range is needed. Another limitations is that other health behaviors may play a role in screen-time and sleep patterns, including sleep arrangement and mealtime habits [ 42 ], and these behaviors may also differ among levels of household chaos. Examination of household chaos with device-based measures of physical activity, sedentary behavior, and sleep, such as accelerometry, may better assess the potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…years, and only one previous study considered diet, physical activity, sedentary behaviour, and sleep concurrently 12 . In addition to including variables on all these lifestyle behaviour in young children, this is also to our knowledge the rst study to include eating behaviour, as opposed to dietary quality.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of studies using CA or LCA to identify patterns of lifestyle behaviours in children and adolescents have found that these behaviours often cluster in complex ways and that group membership differs by gender, age and socio economic status 8,11 . Most previous studies have been conducted in older children, while evidence in young children (< 6 years) is more limited 12,13 . Moreover, few studies have studied diet, physical activity, sedentary behaviour, and sleep simultaneously, with sleep in particular often not included 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…One recent study analysed behavioural patterns at 2 and 5 years of age, and identified two clusters characterised by opposite eating habits at 2 years, while TV was the most distinguishing cluster feature at 5 years. Girls in the cluster defined by high TV exposure were found to have significantly higher body fat at 5 years [ 13 ]. Another study investigating behavioural patterns in 2–9 year olds found that clusters characterised by high sedentary behaviour, low fruit and vegetable intake, sugar-sweetened beverage consumption and low PA were associated with body mass index (BMI) and waist circumference z-scores greater than 1 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%